Modelo de implante de tumor de Walker em cérebro de ratos - Felix, Francisco Hélder Cavalcante (2001)
The disabling effects of central nervous system (CNS) tumors are out of proportion to their low incidence. They’re second only to stroke as neurologic mortality causes. Brain metastases are the commonest intracranial tumors in adults, almost 10 times more frequent than primary brain tumors. Their diagnosis and treatment have met significant advances, although much more research about drug resistance and new treatment modalities are needed. New and even better brain tumor animal models will help to evaluate novel drug regimens and adjuvant therapies for CNS neoplasms. In the present work, the author presents a simple and easily reproducible brain tumor model utilizing the tumor cell line W256 transplanted to Wistar rats. They tested a drug widely used for palliative treatment of tumoral brain edema (dexamethasone), for survival impact. They also have tested the effects of a drug newly proposed as multidrug resistance reversal agent (cyclosporin – CS). Wistar albino rats had stereotaxic intracranial tumor inoculation after the surgical installation of a permanent canulla on the area of interest (right subfrontal caudate). The brain tumor model, as a model of metastatic brain disease, was successful, with reproducible tumor growth (95%), low incidence of extracranial tumor implantation (21% local, no distant metastasis) and few evidence of surgical site infection (21%). The median survival of the animals was 12.5 days (control), 13 days (CS vehicle treated), 11 days (CS treated), 9.5 and 9 days (dexamethasone 0.3 and 3.0 mg/kg/day). These differences were not significant, although the survival rates on the 12th day post-inoculation have showed a significant survival decrease for the case of dexamethasone 3,0 mg/kg/day (p < 0.05), but not for CS treatment (Fischer’s Exact Test). The estimated tumor volume was 17.08 ± 6.7 mm3 (control) and 12.61 ± 3.6 mm3 (CS treatment, not significant, Student’s t-test). The tumor volume in the 9th day post-inoculation was estimated in 67,25 ± 19,8 mm3. The doubling time was 24.25 h. This model behaved as an undifferentiated tumor, with local invasiveness features compared with that of primary brain tumors. It fits well, in this way, for the study of tumor cell migration on CNS parenchyma. Phenomena like neuronal degeneration, neuron cell edema and death, and gliosis, as well as perivascular cell infiltrates, were seen frequently. One could find, also, neoangiogenesis, satellite tumor growth, and tumor cell migration in normal brain parenchyma. Besides heavy parenchymatous infiltration, it was also disclosed markedly tumor cell migration along white matter tracts, such as callosal fibers and infiltration in the Virchow-Robins perivascular space. The model presents as a dual brain tumor and leptomeningeal carcinomatosis model. It could be used for the study and treatment test in the scenario of these two pathologies. The intracerebral tumor growth induced peripheral blood neutrophil count elevation (ANOVA, p < 0.01), higher chance for neutrophilia (Fischer’s Exact Test, p < 0.01), higher chance for lymphopenia (Fischer’s Exact Test, p < 0.01) and brain weight increase (Student’s t-test, p < 0.001) comparing to control. There was no significant change in any of the other hematologic, biochemical and biological parameters tested. CS treatment did not alter any of the tests, as compared to non-treated brain tumor animals. The only exception was the mean animal weight on the first week post-inoculation (ANOVA, p < 0.05). CS, in this way, was responsible for an early cachexia in the brain tumor inoculated animals. CS treatment of brain tumor animals did show non-significant effects indicating a volume (26%) and weight tumor decrease, and tumor infiltrating neutrophil increase (odds ratio - OR = 5.6). This indicates the necessity to further study morphologically and functionally the local inflammation in brain tumor inoculated animals, as well the effects of CS administration. In conclusion, the W256 intracerebral tumor model is simple, easily performed, reproducible and of great potential utility. In this model, tumor inoculation can lead to hematologic and biologic modifications in the experimental animals. CS could apparently lead to early tumor caquexia in this tumor model. However, CS treatment did not modify the survival chance of the brain tumor animals, in sharp contrast to dexamethasone 3.0mg/kg/day, a much-used drug in the treatment of brain tumors, which decreased the animal survival.